The importance of employees’ engagement initiativesin the hospitality industry in Portugal - Moura, Leonor Maria Terruta Marques de (2022)
Dealing with employees’ turnover intent is a current issue in the hospitality world. Covid19 has created anxiety and tensions around the globe, reflecting on multiple layoffs and a greater impact on staff turnover intent. This study aims to examine the effect of employees’ perceived incentives on turnover intention through the mediating role of employees’ satisfaction for a sample of hospitality workers in Portugal. Additionally, it provides important findings regarding the incentives that hotel employees value the most. A set of hypotheses were developed through a conceptual framework based on the literature review. An empirical study was developed by means of anonymously surveying responses from 194 employees, as well people who had work in this sector during the past year. After collecting and analyzing the data through SPSS, it was established direct and positive relationships between the variables under study. Results indicate that perceived incentives, job satisfaction, and turnover intention are significantly associated. Employees’ perceived incentives diminish directly turnover intention, and indirectly through job satisfaction. As the direct effect of perceived incentives is significant, the mediation through job satisfaction is partial. Results also suggest that perceived incentives have a significant effect on employees’ satisfaction and that this relationship diminishes turnover intention. Additionally, confirms that base salary, career development, good work environment, and training and development are the incentives most valued by employees. This study reveals relevant results that will help manage the organizations’ staff and provide social and practical implications concerning employee engagement initiatives on human resource management (HRM) practices.